Imaging Autophagy. Issue 1 (1st July 2014) - Karanasios, Eleftherios; Stapleton, Eloise; Manifava, Maria; Ktistakis, Nicholas T.
Abstract: Autophagy is a membrane‐trafficking pathway activated to deliver cytosolic material for degradation to lysosomes through a novel membrane compartment, the autophagosome. Fluorescence microscopy is the most common method used to visualize proteins inside cells, and it is widely used in the autophagy field. To distinguish it from the cellular background, the protein of interest (POI) is either fused with a genetically encoded fluorescent protein or stained with an antibody that is conjugated to an inorganic fluorescent compound. Genetic tagging of the POI allows its visualization in live cells, while immunostaining of the POI requires the fixation of cells and the permeabilization of cell membranes. Here we describe detailed protocols on how to visualize autophagy dynamics using fluorescence microscopy in live and fixed cells. We discuss the critical parameters of each technique, their advantages, and why the robustness is increased when they are used in tandem. Curr. Protoc. Cytom . 69:12.34.1‐12.34.16. © 2014 by John Wiley & Sons, Inc.